Pelatihan Pembuatan Eco-Enzyme dari Sampah Buah dan Sayur di Kelompok Wanita Tani (KWT) Kota Bandar Lampung - Septiani, Riana; Sundari, Susanti; Suwarni, Putri Endah; Sari, Indah Purnama; Pahlevi, M.Reza; Carolina, Thabita; Suharyono, Heru (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Organic waste is still a problem that needs to be resolved. Piles of organic waste can cause the emergence of methane gas (CH4), giving rise to an unpleasant odor and can even potentially cause disease. The aim of this community service is to provide understanding, knowledge and skills to the community regarding how to utilize household organic waste in the form of fruit and vegetable waste into eco-enzymes by fermentation. eco-enzyme is a multi-purpose liquid that can be used to purify waste water, as a household cleaning product, as a detergent, as a pest control product, to remove pesticide residues, and also as an organic fertilizer for plants. The method used is Participatory Action Research (PAR) where the service team is integrated into the community and works with the community to increase the knowledge and abilities of the people who are members of the Women Farming Group (KWT) in understanding and changing the community to become better, more empowered and knowledgeable. The results of this activity were able to increase the understanding, knowledge and skills of Women Farmer Groups in 4 Districts of Bandar Lampung city both conceptually and practically, and have the awareness not to just throw away organic waste, but to use it because it not only protects the environment but also provides benefits to the community. This activity was considered successful and sustainable for future programs.